Juvenile cemento-ossifying fibroma: a case report using modified Gallego’s staining - Avinash, Tamgadge; Sandhya, Tamgadge; Gokul, Venkateshwar; Neha, Tiwari; Snehal, Dhauskar (International Journal of Research in Medical Sciences, 2016)
Juvenile cemento- ossifying fibroma is a rare benign but locally aggressive tumour with high recurrent potentials. The present study reports a case of juvenile aggressive ossifying fibroma involving the maxilla of a 6year old boy reported with a chief complaint of painless swelling over right side of the cheek since six months without any significant etiological factor. Modified gallego’s staining had been used to differentiate hard tissue deposits in the lesional tissues which have not been implicated so far in any fibroosseous lesions which makes this report unique.